A Model of Electronic Document Management System for Limited Partnership - Faiqunisa Faiqunisa; Eko Nugroho; Paulus Insap Santosa (Universitas Islam Sultan Agung, 2013)
Both types of documents, electronic and non-electronic are a major component supporting activities. In addition to the documents, communications capabilities to employees and managers effectively with other stakeholders are one of the important key achievements of organizational goals. LP. XYZ is one of the Consultants in the field of Information Technology, but the storage and management of electronic documents and archives themselves carried on a server without a management information system, so that records and electronic documents have not been properly managed. This study makes modeling system includes document management of process models, data models and interface models to suit the needs of the LP. XYZ administration in organizing activities, such as enterprise document management, web content management, project management and communication management of work, so the management information system may be supporting the business activities and operations of LP. XYZ.